MODERN PHARMACOTHERAPEUTIC PRINCIPLES OF TREATMENT OF MYOCARDIAL INFARCTION DISEASE - Toshpulatov Sardorjon Sarvar Ogli; Akhmatova Munisa Azamat Kizi; Abdurakhimova Lola Anvarovna (Western European Studies, 2025)
Myocardial infarction is a condition in which the coronary arteries of the heart are blocked by a thrombus or their compression, resulting in necrosis (local death) of the heart muscle as a result of impaired blood supply to the heart muscle. This leads to a disruption of the functioning of the entire cardiovascular system and endangers the patient's life. This disease affects people aged 45-60. Myocardial infarction is an acute condition, a clinical form of ischemic heart disease. This article discusses the clinical picture, prevention and treatment of myocardial infarction
Keywords: Myocardial infarction; coronary embolism; coronary artery spasm